2014
DOI: 10.1539/joh.13-0223-fs
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of the Rate of Stair Use over a Long‐term Period Using a Stair Climbing Campaign

Abstract: Maintenance of the Rate of Stair Use over a Long‐term Period Using a Stair Climbing Campaign: Takuo NOMURA, et al. Department of Rehabilitation Sciences, Kansai University of Welfare Sciences— Objective This study was a long‐term survey of a stair climbing campaign that made use of point‐of‐choice prompts aimed at achieving exemplary behavior in citizens. Methods The campaign began in September 2007 at the Kochi Prefectural Office. We monitored office workers who climbed the stairs or used the elevator in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…More than 50% of older adults in Japan are not engaged in any PA [9]. Japanese health professionals are adopting the Ministry of Health Promotion Movement in the 21st Century (“Health Japan 21”) project, which promotes PA for the citizens of all ages in Japan, particularly targeting increasing the number of steps [10,11] and improving the ability to perform daily living activities [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 50% of older adults in Japan are not engaged in any PA [9]. Japanese health professionals are adopting the Ministry of Health Promotion Movement in the 21st Century (“Health Japan 21”) project, which promotes PA for the citizens of all ages in Japan, particularly targeting increasing the number of steps [10,11] and improving the ability to perform daily living activities [12].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous interventions have been conducted using various approaches, including motivational posters, signs [24,25], videos [26], environmental changes [27] and PA programming [28]. Many interventions promoted stair use settings at worksites [11,29], shopping malls and train stations [30]. A recent systematic review demonstrated the effectiveness of stair use and stair climbing interventions in various public settings [31].…”
Section: Introductionmentioning
confidence: 99%
“…The studies’ characteristics included in the systematic review are available in Supplemental Appendix 2. A total of 17 studies were conducted in Europe (2137), three in Asia (3840), 11 in North America (4151), and three in Oceania (5254). Interventions consisted of prompts (25,27,33,36,37,39,40,41,43,4553,54), posters (21,27,40), banners (25,30), messages, and signs (24,25,28,30,38,44).…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis conducted by Marshall (2004) revealed that the most successful physical activity interventions are those that promote incidental physical activity in and around the workplace. For example, multiple studies have shown that health-related motivational and educational posters, a low-cost option, succeed in increasing the use of stairs in lieu of the elevator or escalator in a variety of settings, including train stations, office buildings, factories, health care clinics, and hospitals (Kwak, Kremers, van Baak, & Brug, 2007; LaCaille et al, 2016; Marshall, Bauman, Patch, Wilson, & Chen, 2002; Nomura, Katayama, Kashiwa, Akezaki, & Sato, 2014). In addition, it has been shown that self-monitoring techniques, which can be achieved with low-cost pedometers and/or cell phone apps, are effective in increasing employee step counts (LaCaille et al, 2016; Michie, Abraham, Whittington, McAteer, & Gupta, 2009).…”
Section: Background/literature Reviewmentioning
confidence: 99%
“…Additionally, the authors are not aware of any study that has objectively measured the impact of a poster campaign on daily physical activity levels. Previous studies have primarily relied on self-report or have limited their measurements to the change in stair use (Eves, Webb, Griffin, & Chambers, 2012; Kwak et al, 2007; LaCaille et al, 2016; Marshall et al, 2002; Nomura et al, 2014). Therefore, the aim of the current study was to complete a pilot investigation on the effects of self-monitoring and a worksite physical activity promotion poster campaign targeting hospital nurses.…”
Section: Background/literature Reviewmentioning
confidence: 99%